ANALISIS KINERJA ANGKUTAN KOTA DI KABUPATEN CIAMIS (Studi Kasus Angkutan Kota 04 di Terminal Ciamis) - maulana, ihya; maskur, atep; sumarno, wahyu (Jurnal Ilmiah Teknik Sipil, 2024)
City transportation is one of several types of public transportation facilities, this city transportation is used to make it easier for people to carry out daily activities such as traveling to shopping centers, workplaces, schools and others. City transportation in Ciamis Regency is available with a variety of various routes. Several transport routes are not running optimally in terms of performance, one of which is route 04 (Ciamis – Benteng) where the number of operating vehicles is not balanced with the actors of the community movement. The purpose of this research is to find out how far the performance of city transportation is at Ciamis Terminal for route 04 (Ciamis – Benteng) and also to find out the factors that influence the performance of city transportation at Ciamis Terminal for route 04 (Ciamis – Benteng). The method used in this study is the observation method by way of direct surveys to the field to obtain data as a reference for research. The results of this research on the performance of city transportation in Ciamis Regency route 04 (Ciamis – Benteng) with a load factor value of 48.61% <70%, this does not meet the standard provisions for passenger loading. Then the factors that affect the performance of this city transportation are the number of fleets realized more while the lack of passengers makes the ideal number of route 04 only 2 transportation, because most people use private vehicles.